Newborn Screening: Education, Consent, and the Residual Blood Spot. The Position of the National Society of Genetic Counselors. Issue 1 (24th July 2013) - Blout, Carrie; Walsh Vockley, Cate; Gaviglio, Amy; Fox, Michelle; Croke, Brook; Williamson Dean, Lori; ,
Abstract: Newborn screening (NBS) is a minimally invasive lifesaving test. There is currently no federal mandate for NBS, thus states determine their own screening panel based on the recommendations of the Secretary's Advisory Committee on Heritable Disorders in Newborn and Children (SACHDNC), which was recently re‐chartered as the Discretionary Advisory Committee on Heritable Disorders in Newborns and Children (DACHDNC). After NBS is completed, a couple of residual blood spots remain. While some states allow these spots to be used for public health and scientific research purposes, parents are not always informed about these additional uses. This paper addresses the National Society of Genetic Counselors' (NSGC's) position about NBS and blood spot storage/use and the rationale for these positions. The National Society of Genetic Counselors strongly supports newborn screening for the uniform screening panel of conditions recommended by the Secretary's Advisory Committee on Heritable Disorders in Newborns and Children. NSGC also supports storage and use of blood spot samples by newborn screening laboratories and transparent policies that govern these activities.